The Role of the Operating Room Nurses in the Treatment of Necrotizing Fasciitis - Lowe, Amoy (Operating Room Nurses Association of Canada Journal, 1997)
The Canadian public heard about necrotising fasciitis - the “Flesh Eating Disease” the week before Christmas, 1994. The media headlines were filled with news of this disease which the premier of Quebec had contracted. Like many professionals in the health care sector we speculated what was happening between each of the news bulletins updating his health. One of the experts frequently quoted by the media was Dr. Donald Low, Microbiologist at Mount Sinai Hospital. The Premier survived his bout with this disease, but had his leg amputated to prevent the spread of the infection.